Diagnostic value of elastic fibers staining in dystrophic epidermolysis bullosa - Min-tong HE; Zeng-qi TANG; Guo-zhen TAN; Zhi-xuan GUO; Qing GUO; Liang-chun WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To investigate the diagnostic value of elastic fibers staining in dystrophic epidermolysis bullosa (DEB) that was diagnosed based on immunohistochemistry staining. Methods: Immunohistochemistry staining was used to examine keratin 14, laminin 5, collagen Ⅳ and collagen Ⅶ in DEB, and Weigert's resorcin-fuchsin staining for elastic fibers was used in DEB and BP. Results: As for 17 cases with DEB, collagen Ⅶ was absent at the dermis-epidermis junction, while keratin 14 and laminin 5 were present at the epidermal side and collagen Ⅳ distributed at the epidermal side or was absent. Elastic fibers were completely absent in papillary and upper dermis in DEB while were reduced only in dermal papillae in BP. Conclusions: DEB can be diagnosed based on the immunohistochemistry staining results of keratin 14, laminin 5, collagen Ⅳ and collagen Ⅶ.According to the different expression patterns of elastic fibers in DEB and BP, elastic fibers staining could be an alternative marker to differentiate them.